Foundations for Efficient Web Service Selection - Yu, Qi.; Bouguettaya, Athman; SpringerLink (Online service) (Boston, MA : Springer US, 2010)
Foundations for Efficient Web Service Selection describes the foundational framework for efficient Web service selection. It lays out a theoretical underpinning for the design of models and algorithms for searching and optimizing access to Web services. Excerpts from Prof. Fabio Casati$1 (Bs foreword: This excellent book looks at the search problem from a broader perspective. Instead of narrowing down on a specific aspect or subproblem of service search, it dissects and analyzes the fundamental problems in search and presents concrete, applicable solutions as well as the theoretical foundations behind them$1! =(BOne aspect I found particularly significant in the book is the mind shift it generates from thinking about service modeling for the sake of supporting deployment or invocation to modeling for supporting search. This design for search approach is exactly what we do when we design databases because search is what we worry about in that case, and there is no reason why this shouldn$1 (Bt be the case for services if we want services to be searchable with a similar effectiveness. Foundations for Efficient Web Service Selection is designed for researchers and practitioners in the service-oriented computing area. This book is also suitable for advanced-level students in computer science.s
Towards a WSMS: The State of the Art -- A Foundational Service Framework -- Multi-objective Service Query Optimization -- Skyline Computation for Multi-Service Query Optimization -- Skyline Computation over Uncertain QoWS -- Related Work -- Conclusions.
Keywords: Computer science; Computer network architectures; Computer Communication Networks; Database management; Information systems; Computer Science; Information Systems Applications (incl.Internet).; Database Management; e-Commerce/e-business.; Computer Communication Networks; Computer Systems Organization and Communication Networks